Assessing the risk of diabetes among healthcare professionals in Mardan: a multicentre cross-sectional study using the QDiabetes® calculator - Syed Arshad Ullah; Hasnain Ali; Saeed Ahmad; Syed Liaquat Ali Shah; Soma Hussain (Journal of the Pakistan Medical Association, 2026)
Objectives: To evaluate the 10-year risk of developing type 2 diabetes mellitus among healthcare professionals using a risk calculator. Method: The cross-sectional study was conducted at four public hospitals in Mardan, Pakistan, from August 2023 to January 2024, and comprised permanently employed healthcare professionals, including doctors, nurses and paramedics, of either gender aged 25-60 years. Data was collected using a modified QDiabetes questionnaire, and biochemical tests were performed. The risk of developing type 2 diabetes mellitus was calculated using QDiabetes risk calculator. Data was analysed using SPSS 22. Results: Of the 232 subjects with mean age 35.3±8.7 years, 145(62.5%) were males and 87(37.5%) were females. The overall mean body mass index was 25.4±4.5kg/m². The mean QDiabetes score was 5.5±8.3%, with 167(72%) having low risk, 16(6.9%) being borderline, 35(15%) having intermediate and 14(6%) having high risk. Higher score was associated with being male, married, paramedic and having a higher body mass index (p<0.05). Age (R=0.59, p<0.001) and body mass index (R=0.64, p<0.001) showed moderate positive correlations with the risk score, while systolic blood pressure (R=0.28, p<0.001) and triglyceride level (R=0.14, p=0.03) had weaker associations. Conclusion: Healthcare workers were found to be at a borderline risk of developing type 2 diabetes mellitus, with paramedics exhibiting a higher risk compared to doctors and nurses. Age and body mass index were significant predictors of the risk, while systolic blood pressure and triglyceride levels had weaker associations. Key Words: Diabetes risk, Type 2 diabetes mellitus, Healthcare professionals, QDiabetes risk calculator, Risk factors.